Earthquake-induced soft-sediment deformation structures in Upper Jurassic open-marine microbialites (Neuquén Basin, Argentina) - Martín Chivelet, Javier (2011)
Penecontemporaneous decimetre-scale soft-sediment deformation structures are reported from the basal part of the Upper Jurassic-Lower Cretaceous Vaca Muerta Formation, in the Malargüe-Las Leñas area of the back-arc Neuquén Basin (Mendoza Province, Central Andes). The deformed interval (Amarillas bed) is only 0.3 to 0.9m thick but occurs in a wide area, larger than 1500km2. Its age, determined by ammonite biostratigraphy, is Early Tithonian.The soft-sediment deformation structures were generated in finely laminated, partially consolidated, organic-rich, carbonate microbialites that were deposited in open-marine, poorly oxygenated settings, apparently devoid of any significant slope. Those structures include boudins of different sizes and complexity, a variety of folds, normal (listric) dm-scale faults, sub-horizontal detachment surfaces and other features, which are part of several larger-scale, complex slump structures. Deformation was dominantly plastic but near to the ductile-brittle field transition.On the basis of the observed soft-deformation structures, their geographic distribution, their lateral homogeneity, and the geodynamic framework of the basin in which it was generated, the Amarillas bed can be tentatively attributed to a large, intermediate-depth earthquake that occurred within the plate that subducted beneath the Andean continental margin and the Neuquén back-arc basin.